Get insightful responses to your questions quickly and easily on IDNLearn.com. Get accurate and detailed answers to your questions from our knowledgeable and dedicated community members.

Let f (x) = -3x + 4. Describe the transformations from the graph of f to the graphs of g(x) = f (x) + 3 and h(x) = f (x - 2).

Sagot :

Answer:

Answer:

g(x)=-6/5x+1/2

h(x)=-6/5x-1/2

Step-by-step explanation:

1).   g(x)=−f(x) ?

f(x)=6/5x−1/2

g(x)=−(6/5x−1/2)

g(x)=-6/5x+1/2

2). h(x)=f(−x) ?

f(-x)=6/5(-x)−1/2

f(-x)=-6/5x-1/2

h(x)=-6/5x-1/2

Step-by-step explanation: